THE PLACE OF DANCE IN THE PRESIDENT'S FIVE KEY INITIATIVES (British Journal of Global Ecology and Sustainable Development, 2024)
In this article, the most enlightened values, human qualities, and national traditions of our people are mentioned in national dances. It was also noted about improving the dance education system, fully covering the need for training qualified personnel, creating new generation textbooks, etc.